The Combined Loss of Triose Phosphate and Xylulose 5-Phosphate/Phosphate Translocators Leads to Severe Growth Retardation and Impaired Photosynthesis in Arabidopsis thaliana tpt/xpt Double Mutants - Hilgers, Elke J. A.; Schöttler, Mark Aurel; Mettler-Altmann, Tabea; Krueger, Stephan; Dörmann, Peter; Eicks, Michael; Flügge, Ulf-Ingo; Häusler, Rainer E. (Frontiers in Plant Science, 2018)
The xylulose 5-phosphate/phosphate translocator (XPT) represents the fourth functional member of the phosphate translocator (PT) family residing in the plastid inner envelope membrane. In contrast to the other three members, little is known on the physiological role of the XPT. Based on its major transport substrates (i.e. pentose phosphates) the XPT has been proposed to act as a link between the plastidial and extraplastidial branches of the oxidative pentose phosphate pathway (OPPP). As the XPT is also capable of transporting triose phosphates, it might as well support the triose phosphate PT (TPT) in exporting photoassimilates from the chloroplast in the light (`day path of carbon´) and hence in supplying the whole plant with carbohydrates. Two independent knockout mutant alleles of the XPT (xpt-1 and xpt-2) lacked any specific phenotype, suggesting that the XPT function is redundant. However, double mutants generated from crossings of xpt-1 to different mutant alleles of the TPT (tpt-1 and tpt-2) were severely retarded in size, exhibited a high chlorophyll fluorescence phenotype, and impaired photosynthetic electron transport rates. In the double mutant the export of triose phosphates from the chloroplasts is completely blocked. Hence, precursors for sucrose biosynthesis derive entirely from starch turnover (`night path of carbon´), which was accompanied by a marked accumulation of maltose as a starch breakdown product. Moreover, pentose phosphates produced by the extraplastidial branch of the OPPP also accumulated in the double mutants. Thus, an active XPT indeed retrieves excessive pentose phosphates from the extra-plastidial space and makes them available to the plastids. Further metabolic profiling revealed that phosphorylated intermediates remained largely unaffected, whereas fumarate and glycine contents were diminished in the double mutants. The assessment of C/N-ratios suggested co-limitations of C- and N-metabolism as possible cause for growth retardation of the double mutants. Feeding of sucrose partially rescued the growth and phorosynthesis phenotypes of the double mutants. Immunoblots of thylakoid proteins, spectroscopic determinations of photosynthesis complexes, and chlorophyll a fluorescence emission spectra at 77 Kelvin could only partially explain constrains in photosynthesis observed in the double mutants. The data are discussed together with aspects of the OPPP and central carbon metabolism.